Titanium, Vanadium and Chromium Transition Metal Schiff Base Complexes with Biological, Catalytic, and Anti-Glycation Activities: A Review - Gervas E. Assey; Raphael Mgohamwende (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Schiff bases are compounds obtained from the condensation reaction of a primary amine and aldehyde or ketone. They can be coordinated with metals especially the transition metals to form Schiff base complexes. The study objectives for this work are: Firstly to review the synthesis, characterization and biological activities of both Schiff base ligands and their transition metal complexes of titanium, vanadium and chromium. Secondly to look into the studies of catalytic activities of both Schiff base ligands and their transition metal complexes of titanium, vanadium as well as chromium. Thirdly to review the anti-glycation activities of aroyl-hydrazine ligands, their chromium (III) complexes and metal salt itself. The methodology used for looking for the references was through the internet. Biological activities that were considered in this review were mainly those of antibacterial and antifungal. For the antibacterial, both gram positive and gram negative strains were considered. The results obtained from the study indicated that the Schiff base complexes, Schiff bases as well as metal ions for the metals titanium, vanadium and chromium were used by different researchers to investigate antimicrobial activities against bacteria, fungi as well as anti-tumour activity against breast cancer. The antimicrobial literature studies showed that the metal ions were having lower inhibition capacity than the ligands but the complexes showed the highest inhibition capacity against the microbial. The use of Mono- and dioxide-vanadium (V) complexes showed anticancer activity against MCF-7 (breast cancer) cells. The cis-Dioxido vanadium (V) complexes were also investigated for catalytic activity on the oxidation of cyclohexane and gave conversion of 12% and selectivity of up to 85%. The paper is divided into five sections which include introduction, methodology used in looking for references, results and discussion, acknowledgements and references. The results obtained from the review show that the Schiff base complexes were more effective when screened as anti-microbial compounds than their ligands. The complexes also showed effectiveness when screened for their catalytic activity on organic chemistry reactions. Chromium (III)-aroyl-hydrazine complexes showed that they are decisive to inhibit the process of protein glycation more efficiently as compared to amino groups complexes.